Say we have this function: $g(x) = 1+ \frac{1}{x+1}$ for $x>-1$.

The question asks to solve for $g(x) = g^{-1}(x)$. I intuitively thought to first calculate the inverse function's equation which turned out to be $y=\frac{-x+2}{x-1}$ and then to simply equate it with the original function (which I thought was the normal way to find POI's of functions). However, while this did produce an answer ($x=0,-2$) they were not correct (the answer is $x=\sqrt{2}$.Could I have some direction on this please.


2 Answers 2


Your method is correct, but you made a mistake when finding the inverse of $g$. To see why, note that $g(0)=2$ but $$ -\frac{(2)+2}{(2)-1} = -4 \ne 0. $$ It should be $$ g^{-1}(x) = \frac{2-x}{x-1}. $$ Let's verify that this is correct. Note that $$ (g\circ g^{-1})(x) = 1+\frac{1}{\frac{2-x}{x-1}+1} = 1+\frac{1}{\frac{1}{x-1}} = 1+(x-1)=x $$ and $$ (g^{-1}\circ g(x) = \frac{2-(1+\frac{1}{x+1})}{(1+\frac{1}{x+1})-1} = \frac{1-\frac{1}{x+1}}{\frac{1}{x+1}} = \frac{1}{\frac{1}{x+1}} -1=(x+1)-1=x. $$

Continuing with the solution, we need to solve $g(x)=g^{-1}(x)$. That is: \begin{align*} 1+\frac{1}{x+1} &= \frac{2-x}{x-1} \\ (x+1)(x-1) + (x-1) &= (x+1)(2-x) \\ (x-1)(x+2) &= (x+1)(2-x) \\ x^2+x-2 &= -x^2+x+2 \\ 2x^2-4&=0 \\ x^2 &= 2 \\ x &= \pm\sqrt{2} \end{align*}

Since the domain excludes $x=-\sqrt{2}$, we are left with only $\sqrt{2}$.

  • $\begingroup$ argh! i made a typo when i was putting this online! on my paper i have it as what i have corrected it to. i am very sorry for wasting your time, but your answer still is insightful $\endgroup$
    – John Hon
    Aug 19, 2017 at 14:50
  • $\begingroup$ @JohnHon No problem. I've added more information. $\endgroup$ Aug 19, 2017 at 14:59

HINT: you have to solve $$1+\frac{1}{x+1}=\frac{1}{x-1}-1$$ and this is equivalent to $$2(x^2-2)=0$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.